In Vitro Thrombogenicity Tests of Factor IX Concentrates - Prowse, C V; Chirnside, A; Elton, R A (Thrombosis and Haemostasis, 1979)
Various factor IX concentrates have been examined in a number of in vitro tests of thrombogenicity. The results suggest that some tests are superfluous as in concentrates with activity in any of these tests activation is revealed by a combination of the non-activated partial thromboplastin time, the thrombin (or Xa) generation time and factor VIII inhibitor bypassing activity tests. Assay of individual coagulant enzymes revealed that most concentrates contained more factor IXa than Xa. However only a small number of concentrates, chiefly those that had been purposefully activated, contained appreciable amounts of either enzyme.